Asymmetric Intramolecular Hydroalkoxylation of Unactivated Alkenes Catalyzed by Chiral N‐Triflyl Phosphoramide and TiCl4†. Issue 6 (10th April 2020) - Zhao, Pengyuan; Cheng, Aolin; Wang, Xinxu; Ma, Jiguo; Zhao, Guoqing; Li, Yingkun; Zhang, Yi; Zhao, Baoguo
Summary of main observation and conclusion: By using a combination of a chiral N ‐triflyl phosphoramide and TiCl4 as the catalyst, a new process for asymmetric intramolecular hydroalkoxylation of unactivated alkenes was developed, producing various chiral tetrahydrofuran derivatives in 51%—99% yields with 30%—71% ee's. Abstract : A combination of N ‐triflyl phosphoramide and TiCl4 challenges asymmetric hydroalkoxylation of unactivated alkenes.